Praktik Penetapan Harga Pada Kegiatan Jual Beli Gabah Di Kecamatan Silaen Kabupaten Toba - Panjaitan, Jesica Debora; Firdaus, Firdaus; Dasrol, Dasrol (Jurnal Ilmiah Wahana Pendidikan, 2025)
Paddy is one of the agricultural commodities that plays an important role in the lives of local communities. Therefore, the buying and selling of paddy holds high economic value and has become a routine activity between farmers and middlemen. In the paddy trade, prices are often unilaterally determined by the middlemen without a fair bargaining process. This imbalance in bargaining positions often places farmers at a disadvantage. Middlemen, as business actors, often engage in unfair competition practices, particularly through price fixing. These middlemen collaborate with one another to form price-fixing agreements in paddy trading activities. Such practices are regulated under Article 5 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The purpose of this study is to examine how price fixing is carried out in the paddy trading activities in Silaen Subdistrict, Toba Regency, which leads to losses for farmers, and to identify the ideal measures that should be taken to ensure farmers’ welfare and justice in the paddy trade in the region.The research method used in this study is empirical or sociological legal research. This type of research involves examining the actual conditions that occur in the field. In this study, the researcher directly conducted fieldwork at the research site to provide a comprehensive and clear picture of the problem being studied. The research was carried out in Silaen Subdistrict, Toba Regency, with farmers and paddy middlemen as the population and sample. The data sources used in this study include primary, secondary, and tertiary sources. Data collection techniques used are interviews and literature review. The results of the study show, first, that there is a patron-client relationship between farmers and middlemen in the paddy trading activities, which leads to farmers’ dependency on the middlemen. Furthermore, the middlemen engage in price fixing through prohibited agreements in the form of oligopolies and cartels. These price-fixing practices violate Article 5 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Second, the ideal effort to ensure that farmers achieve welfare and justice in the paddy trading activities in Silaen Subdistrict, Toba Regency, is through government intervention to address the disparity in paddy prices and to strengthen oversight of monopolistic practices.